2014
DOI: 10.1186/1471-2458-14-998
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal pattern and risk factor analysis of bacillary dysentery in the Beijing–Tianjin–Tangshan urban region of China

Abstract: BackgroundBacillary dysentery remains a major public health concern in China. The Beijing–Tianjin–Tangshan urban region is one of the most heavily infected areas in the country. This study aimed to analyze epidemiological features of bacillary dysentery, detect spatial-temporal clusters of the disease, and analyze risk factors that may affect bacillary dysentery incidence in the region.MethodsBacillary dysentery case data from January 2011 to December 2011 in Beijing–Tianjin–Tangshan were used in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 17 publications
7
31
0
Order By: Relevance
“…As has been mentioned above, the findings of correlation between GDP and infectious diseases have coincided with most previous studies 2,3,9,21,22 , but with only a few exceptions 9,2325 . In those exceptional studies, GDP/GDP per capita was not significant predictor of the infectious diseases (e.g., syphilis, gonorrhoea, malaria and Hepatitis C), however, they still displayed the same signs of correlation as this study did.…”
Section: Resultssupporting
confidence: 87%
“…As has been mentioned above, the findings of correlation between GDP and infectious diseases have coincided with most previous studies 2,3,9,21,22 , but with only a few exceptions 9,2325 . In those exceptional studies, GDP/GDP per capita was not significant predictor of the infectious diseases (e.g., syphilis, gonorrhoea, malaria and Hepatitis C), however, they still displayed the same signs of correlation as this study did.…”
Section: Resultssupporting
confidence: 87%
“…The high incidence rate observed in Beijing and Tianjin could potentially be explained by the high population density and good case ascertainment rates in these two regions [18]. These two regions are also known for having a large transient population who mostly live in suburban areas without proper sanitation and access to clean water [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Children <5 years of age are likely susceptible to bacillary dysentery because of low immune function, lack of previous exposure, and a higher chance of exposure to a Shigella -contaminated environment through play-related activities [24, 25]. The difference in incidence between male and female individuals, especially those <5 years of age may be because male individuals are generally more active than female individuals, and thus have more opportunities to be exposed to environments containing bacteria [19]. Over the study period, we also observed a decrease in the proportion of bacillary dysentery cases identified in individuals 5–19 years of age and a corresponding increase in the proportion of cases in individuals ≥60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission pattern of shigellosis has shifted from water/food-to-person to person-to-person, with high risk groups being particularly men who have sex with other men (MSM) in developed countries [1]. Meanwhile, numerous studies have reported that the incidence in males is higher than that in female [6][7][8]. Does this mean that the transmissibility of shigellosis among males is stronger than that among females?…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
“…Humans are the only natural host for Shigella spp.. In recent years, numerous reports have demonstrated that the incidence of shigellosis within males is higher than that within females [6][7][8]. The incidence of shigellosis, a water/food born disease, is directly related to the hygiene behaviours such as regular hand washing [9].…”
mentioning
confidence: 99%